The Intersection of Blockchain, AI, and Islamic Economic Frameworks: A Scholarly Exploration - Aissyah, Shyty Nur; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2024)
This paper explores the intersection of Blockchain, Artificial Intelligence (AI), and Islamic economic frameworks, focusing on their potential synergy in reshaping modern economic systems while adhering to Shariah principles. With its decentralized and transparent nature, blockchain offers innovative solutions to enhance financial transactions, governance, and trust in various sectors. Conversely, AI holds transformative power for data analytics, decision-making, and automation, opening new avenues for efficiency and innovation. By integrating these technologies into Islamic economic systems, this paper examines how they can promote financial inclusion, ensure ethical transactions, and contribute to the broader goals of Islamic economics, such as justice, equity, and social welfare. The exploration is grounded in a comprehensive review of the scholarly literature, which delves into the opportunities and challenges of implementing Blockchain and AI within a Shariah-compliant framework. Ultimately, this paper seeks to provide a roadmap for future research and practical applications of emerging technologies in the context of Islamic economic thought, fostering a balanced and sustainable approach to economic development in a globalized world.